Utilization of Moringa Seed Powder (Moringa Oleifera) as a Natural Coagulant for Reducing Pollution Parameters in Tofu Wastewater - Ismi Khairunnissa Ariani; Riza Hudayarizka; Rahmi Yorika; Rebecca Olfin Liery Any (Frontier Advances in Applied Science and Engineering, 2024)
The wastewater generated from the tofu industry often contains elevated levels of COD and TSS pollutants. One effective method for treating this wastewater is through the coagulation-flocculation process. Moringa seeds, recognized as a biomass with natural coagulant properties, contain a bioactive compound known as 4αL-rhamnosyloxy-benzyl-isothiocyanate, capable of adsorbing particles present in wastewater. The objective of this study is to assess the efficiency of reducing pollutant parameters (COD, TSS, and Turbidity) in wastewater from the tofu industry by utilizing Moringa seeds as a natural coagulant. The research was conducted using a jar test apparatus with coagulation stirring at 100 rpm and flocculation at 40 rpm for 12 minutes. The study involved varying coagulant doses (2, 3, 4, 5, and 6 g/L of tofu wastewater) and coagulation stirring times (1, 3, and 5 minutes). Based on the results obtained, the optimal stirring duration and dose, as well as the efficiency of reducing each pollutant parameter, were determined. For COD, the optimal conditions were found to be 3 minutes stirring time with a dose of 4 g/L, resulting in an efficiency of 64.88%. Similarly, for TSS parameters, the optimum conditions were achieved with 3 minutes of stirring time and a dose of 4 g/L, yielding an efficiency of 52.71%. Lastly, for turbidity, the most effective conditions were observed with 3 minutes of stirring time and a dose of 4 g/L, with an efficiency of 58.85%.